Acid-base and blood gas parameters in relation to obstetrical assistance in dystocia affected buffaloes - PRABHAKAR, S; NANDA, A S; MIRAKHUR, K K; GHUMAN, S P S (The Indian Journal of Animal Sciences, 2013)
The evaluation of acid-base homeostasis in difficult parturition is vital to the clinical recognition of metabolic disorders to provide correct therapeutic measures. The acid-base status of 6 normally calving and 7 dystocia affected buffaloes subjected to fetotomy (n=3) and caesarean section (n=4) was studied. Changes in acid-base status and blood gas dynamics were suggestive of respiratory acidosis with some metabolic compensation on the day of calving in control buffaloes. On the contrary, dystocia affected buffaloes had mild to distinct metabolic alkalosis which continued during the obstetncal manoeuvring. The alterations in metabolic parameters were compensated on post-manoeuvring days. Decreased oxygen utilization following fetotomy or caesarean section was evident which Improved in fetotomy group on subsequent days, however, caesarean group buffaloes showed tissue hypoxaemia continuously till third post-operative day.